Pet Ownership and Cancer Risk in the Women’s Health Initiative - Garcia, David O. (Cancer Epidemiol Biomarkers Prev, 2016)
BACKGROUND: Pet ownership and cancer are both highly prevalent in the U.S. Evidence suggest associations may exist between this potentially modifiable factor and cancer prevention, though studies are sparse. The present report examined whether pet ownership (dog, cat, or bird) is associated with lower risk for total cancer and site-specific obesity-related cancers. METHODS: A prospective analysis of 123,560 participants (20,981 dog owners; 19,288 cat owners; 1,338 bird owners; and 81,953 non-pet owners) enrolled in the Women’s Health Initiative (WHI) observational study and clinical trials. Cox proportional hazards models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for the association between pet ownership and cancer, adjusted for potential confounders. RESULTS: There were no significant relationships between ownership of a dog, cat, or bird and incidence of cancer overall. When site-specific cancers were examined, no associations were observed after adjustment for multiple comparisons. CONCLUSION: Pet ownership had no association with overall cancer incidence. IMPACT: This is the first large epidemiological study to date to explore relationships between pet ownership and cancer risk, as well as associated risks for individual cancer types. This study requires replication in other sizable, diverse cohorts.